Unraveling the antimicrobial potential of Lactiplantibacillus plantarum strains TE0907 and TE1809 sourced from Bufo gargarizans: advancing the frontier of probiotic-based therapeutics - Huang, Feiyun; Zhao, Yanni; Hou, Yusen; Yang, Yu; Yue, Bisong; Zhang, Xiuyue (Frontiers in Microbiology, 2024)
Introduction: In an era increasingly defined by the challenge of antibiotic resistance, this study offers groundbreaking insights into the antibacterial properties of two distinct Lactiplantibacillus plantarum strains, TE0907 and TE1809, hailing from the unique ecosystem of Bufo gargarizans. It uniquely focuses on elucidating the intricate components and mechanisms that empower these strains with their notable antibacterial capabilities.Methods: The research employs a multi-omics approach, including agar diffusion tests to assess antibacterial efficacy and adhesion assays with HT-29 cells to understand the preliminary mechanisms. Additionally, gas chromatography-mass spectrometry (GC-MS) is employed to analyze the production of organic acids, notably acetic acid, and whole-genome sequencing is utilized to identify genes linked to the biosynthesis of antibiotics and bacteriocin-coding domains.Results: The comparative analysis highlighted the exceptional antibacterial efficacy of strains TE0907 and TE1809, with mean inhibitory zones measured at 14.97 mm and 15.98 mm, respectively. A pivotal discovery was the significant synthesis of acetic acid in both strains, demonstrated by a robust correlation coefficient (cor ≥ 0.943), linking its abundance to their antimicrobial efficiency. Genomic exploration uncovered a diverse range of elements involved in the biosynthesis of antibiotics similar to tetracycline and vancomycin and potential regions encoding bacteriocins, including Enterolysin and Plantaricin. Conclusion: This research illuminates the remarkable antibacterial efficacy and mechanisms intrinsic to L. plantarum strains TE0907 and TE1809, sourced from B. gargarizans. The findings underscore the strains' extensive biochemical and enzymatic armamentarium, offering valuable insights into their role in antagonizing enteric pathogens. These results lay down a comprehensive analytical foundation for the potential clinical deployment of these strains in safeguarding animal gut health, thereby enriching our understanding of the role of probiotic bacteria in the realm of antimicrobial interventions.